Investing foreigners in Eastern Germany : transferring state assets to private owners during the 1990s - Allen, Keith R. 1967- (Studien zur Geschichte der Treuhandanstalt, 2023)
The swift and thorough privatization of eastern Germany did not emanate solely from the West German Federal Republic. This book explores actors from abroad – mainly from western Europe – in four functions: as investors, as advisors and capital providers, and as co-decisionmakers on majorsubsidies provided by German public officials. The aim is not to ascertain what went wrong, or possibly right, in eastern Germany's immersion into an enlarged Federal Republic. Rather, this book shows how market developments within Germany before, during, and after formal reunification must be understood together with parallel actors, events, and interests in western European countries, the European Union, and the United States.